A new genus and species of mites of the family Caraboacaridae (Acari: Heterostigmata) associated with carabid beetles (Coleoptera: Carabidae) from Iran - Hajiqanbar, Hamidreza; Khaustov, Alexander; Kamali, Karim; Saboori, Alireza; Kamali, Hashem (Zootaxa, 2008)
A new genus and species of mites of the family Caraboacaridae (Acari: Heterostigmata), Minicaraboacarus quadridiscalis Hajiqanbar and Khaustov n. gen., n. sp. associated with Cymbionotum semelederi (Chaudoir, 1851) (Coleoptera: Carabidae) is described from Iran. The leg chaetotaxy and solenidiotaxy of mites of the family Caraboacaridae are discussed.